2010
DOI: 10.1177/1464884909355910
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the potential of online news: Suggestions from a study on the relationship between online news advantages and its post-adoption consequences

Abstract: Using data from a national survey, this article explores the relationship between nine common socio-technical advantages of online news and how it is used and alters existing news use habits. The article finds that apart from the ability to ‘have my say to the news media’, all the other attributes — no cost, multitasking, more news choices, in-depth and background information, 24/7 updates, customization, ability to discuss news with peers, and the existence of different viewpoints — have a more or less marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 12 publications
3
27
0
3
Order By: Relevance
“…On the contrary, users seem very attached to the traditional ways of journalism -verifying information before publishing it -reflecting previous research on similar normative issues (Nguyen, 2010;van der Wurff & Schoenbach, 2013).…”
Section: Discussion and Conclusion -The Limited Effect Of Transparencysupporting
confidence: 68%
“…On the contrary, users seem very attached to the traditional ways of journalism -verifying information before publishing it -reflecting previous research on similar normative issues (Nguyen, 2010;van der Wurff & Schoenbach, 2013).…”
Section: Discussion and Conclusion -The Limited Effect Of Transparencysupporting
confidence: 68%
“…There is a trend in communication studies research to try to understand the reasons for online news adoption (Salwen, Garrison & Driscoll, 2005;Nguyen, 2010) and there is general agreement that immediacy predicts the adoption of online news sources. Massey and Levy (1999) have affirmed that immediacy has markedly distinguished online news from its print counterpart.…”
Section: News Consumption and The Goal Of Immediacymentioning
confidence: 99%
“…Karlsson (2011) has further claimed that the practice of instant reporting of online news promotes transparency in journalism. Nguyen (2010) has found that an increase in online news attributes -in terms of 24/7 updates, customized news and no cost -predicts newspaper displacement. He has asserted that immediacy (measured by 24/7 updates) is the central defining characteristic of online news, and his study has revealed that it is the strongest reason for online news adoption and the strongest predictor of the take-up of online news.…”
Section: News Consumption and The Goal Of Immediacymentioning
confidence: 99%
“…Examining online news use in Hong Kong, Chan and Fang [5] factor-analyzed 10 online news features and found that convenience, interactivity and multimedia were the key factors of adoption. Nguyen [6] found that an increase in online news attributes -in terms of 24/7 updates, customized news and no cost -predicts newspaper displacement. The attribute of convenience was found to be a strong predictor of the credibility of online news among politically interested news users [7].…”
Section: Literature Reviewmentioning
confidence: 99%